Gender influences: the role of leg dominance in ACL injury among soccer players. Issue 10 (11th June 2010) - Brophy, Robert; Silvers, Holly Jacinda; Gonzales, Tyler; Mandelbaum, Bert R
Abstract : Objective: This study intends to look at the role of leg dominance in anterior cruciate ligament (ACL) injury risk among soccer (football) athletes. The purpose of this study was to test the hypothesis that soccer players rupture the ACL of their preferred support leg more frequently than the ACL in their preferred kicking leg, particularly in non-contact injuries, despite differences in gender. Design: Retrospective observational study. Setting: Outpatient orthopaedic practice. Patients: Subjects who had sustained an ACL injury due to direct participation in soccer. N=93 (41 male, 52 female). Interventions: These noncontact injuries were sustained while playing soccer. Results: For non-contact injuries, roughly half of the injuries occurred in the preferred kicking leg (30) and the contralateral leg (28). However, by gender, there was a significant difference in the distribution of non-contact injury, as 74.1% of males (20/27) were injured on the dominant kicking leg compared with 32% (10/31) of females (p<0.002). Conclusions: When limited to a non-contact injury mechanism, females are more likely to injure the ACL in their supporting leg, whereas males tend to injure their kicking leg. This research suggests that limb dominance does serve as an aetiological factor with regard to ACL injuries sustained while playing soccer. If follow-up studies confirm that females are more likely to injure their preferred supporting leg, future research should investigate the cause for this discrepancy, which could result from underlying gender-based anatomical differences as well as differences in neuromuscular patterns during cutting manoeuvres or kicking.